From ex-soldiers to traders and transporters: the case of the Gold Coast Hausa Constabulary: 1874-1942 - Ntewusu, Samuel Aniegye (2014)
The article discusses the transformation of ex-soldiers in the Gold Coast Hausa Constabulary, later Gold Coast Regiment into traders and transporters in Accra. The argument of the paper is that the ex-soldiers were able to do such a quick transition because of their exposure to transport systems and certain products whiles in active service. Furthermore, they were successful as transporters and traders because of the expansion of Accra which was due to population growth mainly triggered by migrations into the city.